Dynamic trajectories of land use and land cover changes in Lombok Island, West Nusa Tenggara, Indonesia - H. Oğuz Çoban; Miftahul Irsyadi Purnama (Turkish Journal of Forestry)
This study investigates the dynamic trajectories of land use and land cover (LULC) changes in Lombok Island, West Nusa Tenggara, Indonesia, from 2013 to 2022. Utilizing Landsat satellite imagery and a combination of land cover classes from the Indonesian Ministry of Environment and Forestry (MoEF) with the machine learning-based Random Forest algorithm, we aimed to improve classification accuracy and model land cover transitions over time. Intensity analysis was used to measure the impact of population-related land use changes, while trajectory analysis quantified the directional shifts in land cover was employed to quantify and characterize these changes. The analysis highlights substantial transitions from primary and secondary forests to agricultural lands and urban areas, driven by urbanization, population growth, and infrastructure development. Specifically, the period saw a significant forest loss of 28,095 hectares, accounting for 24% of the total forest area, alongside a modest forest gain of 2,453 hectares, indicating ongoing environmental pressures. Despite conservation efforts, rapid economic growth continues to threaten Lombok's forest ecosystems. These findings underscore the urgent need for sustainable land management policies to balance development and ecological preservation while mitigating future forest losses.